New Directions in Supernatural Horror Literature The Critical Influence of H. P. Lovecraft (Springer International Publishing, 2018)
This collection of essays examines the legacy of H.P. Lovecraft's most important critical work, Supernatural Horror in Literature. Each chapter illuminates a crucial aspect of Lovecraft's criticism, from its aesthetic, philosophical and literary sources, to its psychobiological underpinnings, to its pervasive influence on the conception and course of horror and weird literature through the twentieth and early twenty-first centuries. These essays investigate the meaning of cosmic horror before and after Lovecraft, explore his critical relevance to contemporary social science, feminist and queer readings of his work, and ultimately reveal Lovecraft's importance for contemporary speculative philosophy, film and literature.